Striking out. Series 1 [videorecording (DVD)]. - Huberman, Amy; Keenan, Rory; Morrissey, Neil (Acorn, 2017)
Tara Rafferty is a high-flying solicitor living an apparently charmed existence with her good-looking law-partner fiancé Eric. But when she discovers Eric is cheating on her with a colleague, she decides to go it alone and start her own law firm.